Influence of modification of the solid component on the properties of non-autoclaved aerated concrete - Krylov, Eugene; Martynov, Volodymyr; Mykolaiets, Maksym; Martynova, Olena; Vietokh, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2019)
This paper reports results of research into the modification of a solid component in the non-autoclaved aerated concrete with a lime-carbonate additive that contains calcium carbonate (calcite), calcium hydroxide (portlandite) and the additive with a plasticizing and accelerating effect in order to improve its strength. Based on an analysis of the scientific literature, it has been suggested that the properties of cellular concretes are defined by the character of a solid component. The object of research that we selected was the non-autoclaved aerated concrete with a density of 500 kg/m3. The list of raw materials and their characteristics is provided. The aerated concrete was molded at a fixed water demand corresponding to the spread of a mixture of 220 mm by a Suttard viscometer. In the course of experimental study we applied both standard and original test methods (mathematical-statistical methods, x-ray phase analysis, determining the equipotential field of the surface of samples of aerated concrete). We have obtained the non-autoclaved aerated concrete with a modified solid component, which has a maximum compressive strength of 3.53 MPa corresponding to concrete of class C2 in line with current standard. The high strength is explained, based on data from an X-ray phase analysis, by the presence of crystalline phases, which are represented by stable new structures in the form of calcium carbonate and its modifications: vaterite ‒ μ-form of СaСO3, aragonite ‒ metastable form of СaСO3 and tobermorite gel. Based on the data obtained, we have constructed experimental-statistical models of the examined properties. A specific relationship has been established between the strength of non-autoclaved aerated concrete and the equipotential field strength. The research results have been implemented industrially for manufacturing articles from non-autoclaved aerated concrete, which are not inferior, in terms of strength, to its autoclaved analogs.